Leadership Strategies Of Scout Leaders In Instilling The Value Of Descipline In Scout Members - Pardosi, Flora Elsita; Sanjaya, Dicky; Naibaho, Amelya Katrina (Universitas Dharmawangsa Medan, 2025)
Discipline is one of the core character values that students must possess to face the challenges of modern life. In the context of non-formal education, the Scout Movement plays an essential role in instilling character values such as discipline, responsibility, and independence. This study aims to analyze the leadership strategies of the Scout Leader in instilling discipline among members of the Scout organization at UPT SMP Negeri 27 Medan. This research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation. The results revealed that the leadership of the Scout Leader plays a significant role in shaping members' discipline through three main strategies: exemplary leadership, participatory leadership, and moral coaching. Exemplary leadership emerged as the most influential strategy as it fosters self-awareness and voluntary discipline among members. Through open communication and an empathetic approach, the leader successfully created a conducive environment for developing sustainable disciplinary character within the scouting context.